2023
DOI: 10.1038/s41417-023-00590-6
|View full text |Cite
|
Sign up to set email alerts
|

Suicide gene strategies applied in ovarian cancer studies

Abstract: Ovarian cancer represents the most lethal gynecological malignancy among women in developed countries. Despite the recent innovations, the improvements in the 5-year survival rate have been insufficient and the management of this disease still remains a challenge. The fact that the majority of patients experience recurrent or resistant disease have substantiated the necessity of an innovative treatment. Among various strategies investigated, the recent strides made in gene delivery techniques have made gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Various suicide gene candidates cause host cell death by directly inducing apoptosis, or indirectly by converting prodrugs to toxic metabolites. 32…”
Section: Bacteriophage Applications In Medical Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Various suicide gene candidates cause host cell death by directly inducing apoptosis, or indirectly by converting prodrugs to toxic metabolites. 32…”
Section: Bacteriophage Applications In Medical Oncologymentioning
confidence: 99%
“…Phage can be used as a tool for “suicide gene therapy,” the most commonly used approach for solid tumors. Various suicide gene candidates cause host cell death by directly inducing apoptosis, or indirectly by converting prodrugs to toxic metabolites 32 …”
Section: Bacteriophage Applications In Medical Oncologymentioning
confidence: 99%
“…Particularly, this system contemplates the delivery (with viral or non-viral vectors) of a transgene (viral or bacterial) into tumor cells in order to activate a prodrug or to express the “suicide” gene product in the targeted tumor cells (Fig. 5 ) [ 226 ]. However, this strategy is not completely free from toxic effects.…”
Section: Genome Editing and Hypoxia-response Pathwaymentioning
confidence: 99%
“…TRAIL induces cell death upon ligation with its death receptors (Singh et al, 2021). The discovery of its potential to explicitly target malignant cells while sparing normal cells has been met with great enthusiasm, even though the underlying mechanisms have not yet been thoroughly understood (Nguyen et al, 2023). It has been reported that most primary and residual ovarian tumors expressed at least one TRAIL death receptor (DR4 and DR5), while in residual tumors following chemotherapy, one of the two death receptors of TRAIL—DR5 was more frequently observed (Arts et al, 2004; Dong et al, 2008; Duiker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Two targeted therapies have been approved by FDA and EMA, namely, poly‐ADP‐ribose polymerase inhibitors and anti‐vascular endothelial growth factor monoclonal antibodies (Guan & Lu, 2018). In recent years, cancer gene therapy has also attracted great attention owing to the continued progress made in nucleic acids delivery techniques (Nguyen et al, 2023). However, the application of gene therapy as monotherapy in the treatment of ovarian cancer has not been as successful as had been expected (Áyen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%